Aplikasi Pupuk Hayati Konsorsium Dan Inokulan Padat Trichoderma harzianum Terhadap Produktivitas Tanaman Sawi Pada Lahan Terkontaminasi Rhizoctonia solani - A Marthin Kalay; M Riadh Uluputty; Juniart Leklioy; Reginawanti Hindersah; Abraham Talahaturuson (Agrologia, 2016)
Choy sum (Brassica rapa L.) cultivation main obstacle in Maluku was soil fertility and plant diseases. Biological agent and Biofertilizers will play a significant role to reduce the intensity of disease attacks, and increase crop productivity. The objective of this experiment  was to study the effects of nitrogen fixing and phosphate solubilizing microbe (Bion-UP) and Trichoderma harzianum solid inokulan (Bokelas Plus) on choy sum productivity grown on land Rhizoctonia solani-contaminated land. The experimental treatments  were liquid  biofertilizer and Bokelas Plus which has been combined into 6 treatments: Without biofertilizer and Bokelas Plus, 50 kg Bokelas Plus/ha without biofertilizer, 15 mL biofertilizer per plant without Bokales Plus, 15 mL biofertilizer per plant + 50 Kg Bokelas Plus/ha, 15 mL biofertilizer  per plant + 25 kg Bokelas Plus/ha, and 7.5 mL biofertilizer per plant + 50 kg Bokales Plus/ha. The results showed that giving of Bokelas Plus and biofertilizer with different dose levels decreased  leaf blight intensity and increasing fresh weight of choy sum. Biofertilizer application with and without Bokelas Plus decreased the intensity of leaf blight disease by 39.14% - 46, 93%, and increase the fresh weight of choy sum by 15.19% - 36.25%.